The Impact of Technological Advancements on Higher Education: A Study of Generation Alpha’s Educational Prospects - Coolsaet, Dan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The present-day environment is experiencing a rapid technological evolution that fundamentally shifts our understanding of knowledge into a more accessible and open entity. This transformative progression is redefining the practical application of competencies, concepts, and insights and exerting a profound impact on various facets of education. This paradigmatic transition, catalyzed by the pervasive influence of technology, is particularly pertinent in education, where its metamorphic contributions are conspicuously manifest. As the educational milieu continues to undergo metamorphosis, the future pedagogical and didactic methodologies will inevitably bear the indelible imprint of technological advancements. Concurrently, educators are confronted with the distinctive imperative of effectively engaging the emergent cohort of learners, commonly referred to as Generation Alpha, within the context of higher education. A pronounced entrepreneurial disposition characterizes Generation Alpha and is notably predisposed to embracing innovation and advancement, with a significant proportion of its members harboring aspirations of pursuing tertiary education. The present study undertakes a proactive stance in envisioning the educational dynamics and prospects that will define the forthcoming landscape of higher education, with a focal lens on the distinctive attributes of Generation Alpha. This entails a comprehensive inquiry into their favored pedagogical modalities, cognitive perspectives, and educational anticipations. The study embraces a robust theoretical framework anchored in the distinctive attributes of Generation Alpha, attributes invariably molded by the inexorable march of technological progress. In a complementary manner, the study derives insights from a triad of discrete empirical investigations conducted across diverse locales, including New Zealand, Iran, Iraq, and Jordan.